PENERAPAN PIJAT OKSITOSIN PADA MASA NIFAS UNTUK MEMPERCEPAT INVOLUSI UTERI DAN MELANCARKAN PENGELUARAN ASI (Jurnal Kesehatan Siliwangi, 2021)
The postpartum period is a vulnerable period for the mother, because at this time the reproductive organs recover after pregnancy and childbirth. If during recovery there are abnormal changes it will cause complications that can threaten the mother's life. About 60% of maternal deaths occur after delivery of which are caused by complications during the puerperium, one of which is bleeding. To prevent postpartum hemorrhage, you can facilitate the mother to do oxytocin massage, oxytocin massage helps the release of the hormone oxytocin which can cause uterine contractions and affect the process of releasing breast milk smoothly. The purpose of this study was to determine the effectiveness of oxytocin massage on uterine involution and milk ejection. This study refers to the results of a case study of comprehensive midwifery care carried out in Subang with a respondent of one postpartum mother with a background of never getting oxytocin massage in her first child pregnancy and not exclusive breastfeeding, in her second child pregnancy when continuous oxytocin massage has been carried out and causes involution. The mother's uterus becomes normal and faster compared to the first child's puerperium and the release of breast milk becomes smooth, so that the mother avoids postpartum hemorrhage and can breastfeed her baby exclusively.